Leveraging autonomous pedagogical space for technology-transformed learning: a Singapore's perspective to sustaining educational reform within, across and beyond schools. (2015) - Toh, Yancy; Jamaludin, Azilawati; He, Sujin; Chua, Paul Meng-Huat; Hung, David Wei Loong
This paper discusses the dialectical relationship between bottom-up and top-down forces coalescing around the three elements of socio-technical landscape, socio-technical regimes and niche innovations. By studying this intricate connection, we hope to distil how regime-level actors such as policy-makers can influence learning through the introduction of various national policies and how technology-transformed learning that emerged from innovative niches might have the potential to affect the socio-technical (patchwork of) regimes and change the socio-technical landscape. Through a case study of an ICT prototype school in Singapore, we hope to demystify how the climate of increasing school autonomy can afford schools with common meta-language and pedagogical spaces to both tinker and sustain the use of mobile technologies for teaching and learning. The conditions underpinning this multi-level sustainability are unpacked and recommendations made so that typical schools can also experience the opportunities for transformation through spillover effects emanating from networked niches.